2016
DOI: 10.1002/ep.12327
|View full text |Cite
|
Sign up to set email alerts
|

Two‐phase flow simulation of supersaturated total dissolved gas in the plunge pool of a high dam

Abstract: Total dissolved gas (TDG) supersaturation can cause potentially fatal Gas Bubble Disease (GBD) in fish and is recognized for its severe environmental impact for high‐dam operation conditions. The generation of supersaturated TDG in high‐head hydropower project is substantially different from middle‐ or low‐head projects that have been previously studied. Although the mechanics of TDG generation in a plunge pool are clearly three‐dimensional (3D), there are great challenges and difficulties of the 3D simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In addition, Ma et al. (2016b) used the established computational fluid dynamics software to develop a 2D model of two‐phase flow in the plunge pool downstream of a high dam and developed a new simulation module to explain the normal distribution of bubble size. However, a 2D simulation may not always accurately depict the actual flow conditions due to the intricacy of the dam's downstream flow.…”
Section: Research Methods For Tdg Supersaturationmentioning
confidence: 99%
“…In addition, Ma et al. (2016b) used the established computational fluid dynamics software to develop a 2D model of two‐phase flow in the plunge pool downstream of a high dam and developed a new simulation module to explain the normal distribution of bubble size. However, a 2D simulation may not always accurately depict the actual flow conditions due to the intricacy of the dam's downstream flow.…”
Section: Research Methods For Tdg Supersaturationmentioning
confidence: 99%
“…Total dissolved gas (TDG) supersaturation occurs downstream of high dams, especially when discharging abnormally high amounts of water (Qu et al, 2011). Previous studies found that various fish species suffered from gas bubble disease (GBD) due to TDG supersaturation (Qian et al, 2016). Under the influence of GBD, the blood vessels can be clogged with gas bubbles or emboli, resulting in the death of fish (Bouck, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…However, owing to insufficient knowledge of these processes, certain parameters may be neglected in the TDG prediction, leading to an increase in the error of the TDG prediction and restriction of the application range of the model 10 18 . Moreover, considerable calculations must be performed when implementing numerical models, and limited understanding of the two-phase flow movement, bubble transfer process and bubble density distribution may reduce the generality of such models 19 23 . Recently, alternative methods such as neural networks and high-order response surface methods have been used to model the generation of TDG by spilling 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%